Kaspaze - Pižem, Jože (Medicinski razgledi, 2001)
Caspases are cysteine proteases, which cleave their substrates following an aspartate residue. They are present as inactive precursors (pro-caspases) in cells. Caspases are involved in cytokine processing and apoptosis (programmed cell death) regulation. Apoptotic caspases are activator caspases (caspases 8 and 9) or effector caspases (caspases 3 and 7). Apoptosis can be initiated by either extracellular or intracellular pathways. Extracellular signals mediate apoptosis by death receptors, which activate caspase 8. Intracellular signals provoke changes in the permeability of the outer mitochondrial membrane which permits cytochrome C release from mitochondria. In the cytosol, cytochrome C allows activation of caspase 9. Activated caspases 8 and/or 9 induce cascade activation of effector caspases which cleave different target proteins. Demolition of target proteins plays an important role in morphological changesof apoptotic cells.
Keywords: Apoptoza; Cysteine proteinases; Citokini; Apoptosis; CD8-pozitivni limfociti T; Aspartame; Celice ubijalke naravne; Cytokines; fiziologija; T-lymphocytes, cytotoxic; Killer cells, natural; celice; biokemija; Aspartam; kaspaze